Design and synthesis of ice-templated PSA cryogels for water purification : towards tailored morphology and properties - Krantz, William B. (2013)
Hydrogels are capable of absorbing water several times their dry mass that subsequently can be released by the application of pressure, temperature change, or other external stimuli. As such, they offer promise for providing potable water in disaster relief applications. However, the swelling and mechanical properties of hydrogels need to be improved. The objectives of this study were (i) to demonstrate that the properties of poly(sodium acrylate) (PSA) cryogels can be tuned by modulating synthesis conditions such as freezing temperature, initial monomer and initiator concentrations, and crosslinker ratio, and (ii) to investigate the potential of PSA cryogels as an integral membrane for water purification in emergencies. PSA cryogels with a superfast swelling rate and a high degree of swelling that can withstand large compression strains were synthesized by conducting copolymerization reactions between N,N0- methylenebis(acrylamide) and sodium acrylate under subzero temperature conditions. The pore morphology was characterized using confocal laser scanning microscopy and scanning electron microscopy. It was shown that a lower freezing temperature and reduced initial monomer concentrations formed PSA cryogels with smaller more interconnected pores, while a higher initiator concentration in the “freezing before gelation” mode resulted in smaller pores. PSA cryogels with open interconnected pores had both a higher rate and degree of swelling, and high elasticity in response to compression. The separation efficiency of PSA cryogels was evaluated by determining turbidity removal over five operational cycles. The turbidity removal efficiency of the PSA cryogel having the highest swelling degree increased to 90% towards the fifth cycle. The water recovery during the five operational cycles ranged from 71 to 77% under a vacuum suction of 70 kPa (absolute pressure) for one minute. PSA cryogels having smaller average pore sizes were found to have higher turbidity removal efficiencies.